Correlation between head shape and volumetric changes following spring-assisted posterior vault expansion. Issue 4 (April 2022) - Ramdat Misier, Karan R.R.; Breakey, Richard W.F.; van de Lande, Lara S.; Biffi, Benedetta; Knoops, Paul G.M.; Schievano, Silvia; Caron, Cornelia J.J.M.; Dunaway, David J.; Koudstaal, Maarten J.; Jeelani, N.U. Owase; Borghi, Alessandro
Abstract: The aim of the study was to investigate whether different head shapes show different volumetric changes following spring-assisted posterior vault expansion (SA-PVE) and to investigate the influence of surgical and morphological parameters on SA-PVE. Preoperative three-dimensional skull models from patients who underwent SA-PVE were extracted from computed tomography scans. Patient head shape was described using statistical shape modelling (SSM) and principal component analysis (PCA). Preoperative and postoperative intracranial volume (ICV) and cranial index (CI) were calculated. Surgical and morphological parameters included skull bone thickness, number of springs, duration of spring insertion and type of osteotomy. In the analysis, 31 patients were included. SA-PVE resulted in a significant ICV increase (284.1 ± 171.6 cm 3, p < 0.001) and a significant CI decrease (−2.9 ± 4.3%, p < 0.001). The first principal component was significantly correlated with change in ICV (Spearman ρ = 0.68, p < 0.001). Change in ICV was significantly correlated with skull bone thickness (ρ = −0.60, p < 0.001) and age at time of surgery (ρ = −0.60, p < 0.001). No correlations were found between the change in ICV and number of springs, duration of spring insertion and type of osteotomy. SA-PVE is effective for increasing the ICV and resolving raised intracranial pressure. Younger, brachycephalic patients benefit more from surgery in terms of ICV increase. Skull bone thickness seems to be a crucial factor and should be assessed to achieve optimal ICV increase. In contrast, insertion of more than two springs, duration of spring insertion or performing a fully cut through osteotomy do not seem to impact the ICV increase. When interpreting ICV increases, normal calvarial growth should be taken into account.